The Juridical Implications of Cancellation A Marriage Agreement - Marsono, Marsono (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The aim of the research is to find out and analyze the juridical implications of canceling the marriage agreement made by a Notary, and to find out and analyze the legal consequences arising from the cancellation of the marriage agreement made by a Notary due to the non-fulfillment of the objective elements in the marriage requirements. This research is a qualitative research with a sociological juridical approach. The assets acquired during the marriage are in the form of land acquired during the marriage if both parties carry out a mixed marriage or marriage between different nationalities the land must be released because there has been a mixture of assets in which Indonesian citizens will lose their rights to their land. The legal consequences arising from the cancellation of the marriage agreement made by a Notary due to the non-fulfillment of the objective elements in the conditions of marriage for the husband and wife concerned after a District Court order is issued, namely returning to its original state before the existence of the agreement, as well as the creation of a joint property union between the husband and wife. While the inheritance will remain under the control of each party that brought it into marriage. It is suggested that the marriage agreement should be made based on the agreement of the parties and set forth in an authentic deed made by a notary so that the agreement has perfect and permanent legal force and is binding for both parties. Legal consequences with the cancellation of the marriage agreement that has been stipulated, for prospective married couples who want to make a marriage agreement in order to better understand all the consequences that will be received after the marriage agreement applies between them.Keywords: Agreement; Canceling; Marriage.